Identifying the source of gold geochemical anomalies in Jiaodong, eastern China: Tracking the occurrence of gold nanoparticles in a metallogenic system - Li, Ruihong; Wang, Xueqiu; Zhang, Bimin; Liu, Qingqing; Chi, Qinghua; Meng, Yinsheng; Xiong, Yuxin (Frontiers in Earth Science, 2022)
The geochemical anomaly shows good potential for the prospecting of gold deposits all around world. More than 80% of the discovered gold resources are located at geochemical related anomaly area in Jiaodong, which are associated with particle matter. However, it has been known little about the relationship between the occurrence of gold nanoparticles and their geochemical anomaly in multimedia accommodating to the detailed process of gold mineralization system and geochemical exploration. Micro- to nanoscale gold as nanoparticles are related to the hydrothermal fluid flows and precipitation among elemental migration. This paper constructed the fundamental link to geochemical anomaly distribution maps of gold in drainage sediments, wall rocks, and ore, aimed to identify the source of primary and secondary geochemical anomalies according to careful observation at nanoscale gold and revealed the genesis of gold mineralization and their potential in Jiaodong. It has provided important evidence by these micro- to nanoscale gold particles to understand the process of massive gold accumulation and the further prospecting in the Jiaodong Peninsula.